THE ECONOMIC VALUE OF TRIFOLIUM REPENS L. (PALL.) FROM THE FABACEAE LINDL FAMILY. WILD RELATIVES OF CULTIVATED PLANTS OF THE REPUBLIC OF KARAKALPAKSTAN (American Journal of Interdisciplinary Research and Development, 2023)
The article describes the economic value of Trifolium repens L. A moisture-loving and light-loving winter-hardy plant that grows well on soils of different fertility. It grows in the valley and delta of the Amu Darya; it is found along the banks of ditches, in gardens, damp wetlands, as well as among crops. Geographic type: Paleoarctic. It is a valuable plant, it is used as a medicinal, food, industrial, fodder and melliferous plant.